Intercomparison of three microwave/infrared high resolution line-by-line radiative transfer codes. (May 2018) - Schreier, Franz; Milz, Mathias; Buehler, Stefan A.; von Clarmann, Thomas
Highlights: Assessment of equivalent brightness temperatures for the HIRS Channels and "Garand atmospheres". Mutual differences generally in the sub-Kelvin range. Impact of continuum absorption, line-by-line optimization schemes, path integration and discretization. Abstract: An intercomparison of three line-by-line (lbl) codes developed independently for atmospheric radiative transfer and remote sensing – ARTS, GARLIC, and KOPRA – has been performed for a thermal infrared nadir sounding application assuming a HIRS-like (High resolution Infrared Radiation Sounder) setup. Radiances for the 19 HIRS infrared channels and a set of 42 atmospheric profiles from the "Garand dataset" have been computed. The mutual differences of the equivalent brightness temperatures are presented and possible causes of disagreement are discussed. In particular, the impact of path integration schemes and atmospheric layer discretization is assessed. When the continuum absorption contribution is ignored because of the different implementations, residuals are generally in the sub-Kelvin range and smaller than 0.1 K for some window channels (and all atmospheric models and lbl codes). None of the three codes turned out to be perfect for all channels and atmospheres. Remaining discrepancies are attributed to different lbl optimization techniques. Lbl codes seem to have reached a maturity in the implementation of radiative transfer that the choice of the underlying physical models (line shape models, continua etc) becomes increasingly relevant.